The Development of Ornamental Variety of Songko’ Pamiring as a Response to Market Demand - Alimuddin, Alimuddin; Rohidi, Tjetjep Rohendi (Universitas Negeri Semarang, 2018)
Ornamentation on Songko’ Pamiring, as headgear equipment in the Bugis tradition, develops according to the demands of the times. Functionally, Songko' Pamiring is still used as a customary tool but has undergone changes especially in the form of its ornamentation. This study aims to study the design of songkok as an applied visual product that focuses on the ornamental variety of songko' pamiring made by traditional craftsmen who live in Paccing Village, Bone Regency. The study was carried out using qualitative research methods, and interdisciplinary approaches. The results show that there have been changes of orientation in making songko' pamiring. The changes include (1) the form, type, and symbolic meaning of songko' pamiring ornamentation, (2) the weaving techniques using additional media, and (3) the ornamental motifs that have become increasingly simple. In general, these changes are due to changes in orientation in working to meet market demand.